0345 Poor Sleep Health in Informal Caregivers Mediated by Depressed Affect. (27th May 2020) - Marino, V R; Lee, S; Haley, W E
Abstract: Introduction: Informal caregiving has been linked to higher perceived stress. Caregiving stress may be associated with poor sleep. Studies report low sleep quality among caregivers, however, little is known about whether informal caregivers have poorer sleep health than non-caregivers across multiple sleep dimensions. Less is known about whether potential poor sleep health in informal caregivers is explained by depressed mood. This study examined the mediating effect of depressed affect on the relationship between caregiving status and multidimensional sleep health. Methods: 208 current informal caregivers were compared to 3, 342 non-caregivers from the Midlife in the United States study ( M age =55.77±12.29). Using seven domains of sleep (i.e., regularity, satisfaction in sleep, alertness, sleep duration, sleep latency, insomnia, and chronic sleep problems), a composite score of sleep health was constructed using clinically-relevant and previously-used cutoffs ( Range =0-7; higher scores indicating better sleep health). Depressed affect was measured by a continuous scale based on 7 items. The Hayes PROCESS macro with bootstrapping method was used to test mediation with sociodemographic covariate adjustment. Results: Caregivers had poorer sleep health than non-caregivers (β = -0.17; 95% CI = [-.331, -.016]). This association was mediated by depressed affect (indirect effect = -.026; 95% CI = [-.061, -.000]). Specifically, caregiving status was associated with greater depressed affect (β = 0.234; 95% CI = [.019, .450]) and greater depressed affect was associated with poorer sleep health (β = -.112; 95% CI = [-.136, -.089]). The direct effect of caregiving status on sleep health was attenuated when the mediator was considered (β = -0.148; 95% CI = [-.303, -.008]) indicating full mediation. Conclusion: Compared to non-caregivers, informal caregivers have poorer sleep health, and this is mostly due to their greater depressed affect. Stress adaptation techniques such as mindfulness and positive reappraisal may promote better sleep health in informal caregivers through improved affect. Support: N/A